2019
DOI: 10.1016/j.anbehav.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking animal social complexity measures with the help of complex systems concepts

Abstract: Explaining how and why some species evolved to have more complex social structures than others has been a long-term goal for many researchers in animal behavior because it would provide important insight into the links between evolution and ecology, sociality, and cognition. However, despite long-standing interest, the evolution of social complexity is still poorly understood. This may be due in part to researchers focusing on the feasibility of quantifying aspects of sociality, rather than what features are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 77 publications
0
47
0
Order By: Relevance
“…2012 ). Multilayer networks, however, can contain an even wider range of social units—they can simultaneously represent micro-level interactions, higher-level patterning of interactions into relationships and individual roles, macro scale structure across the whole group such as dominance hierarchies, and finally the entire group structure across all social domains, all of which are important components of sociality ( Hobson et al. 2019 ).…”
Section: Measuring Social Structurementioning
confidence: 99%
See 1 more Smart Citation
“…2012 ). Multilayer networks, however, can contain an even wider range of social units—they can simultaneously represent micro-level interactions, higher-level patterning of interactions into relationships and individual roles, macro scale structure across the whole group such as dominance hierarchies, and finally the entire group structure across all social domains, all of which are important components of sociality ( Hobson et al. 2019 ).…”
Section: Measuring Social Structurementioning
confidence: 99%
“…If uniquely assigned to individuals, interlayer edges can help preserve more detail about how individuals are likely to behave and represent individual differences in a more detailed way. Researchers can represent “types” of individuals in ways that match the differentiation a species is able to make among group members given their cognitive abilities ( Hobson et al. 2019 ), or in ways that reflect functionally different contributions to group dynamics.…”
Section: The Functional Parts Of a Multilayer Social Networkmentioning
confidence: 99%
“…When individuals interact in a group, their previous experience, motivation and physiological state (termed here as internal state) affect their action selection, giving rise to diverse activity levels, behavioral responses, and engagement with others [6][7][8] . This results in a highly complex and ever changing environment, where each interaction can change the social context of subsequent interactions, leading to a variety of behavioral outcomes from what seem to be identical starting conditions 7,9 . The complex nature of this environment imposes conceptual challenges in the quantification and analysis of group behavior 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A great many studies on a variety of species, ranging from insects to nonhuman primates demonstrated the complexity of social structures in the animal kingdom 13 , 14 . Particularly for nonhuman primates, who are living in complex social societies, using a variety of strategies and behaviours to interact and connect with each other 15 , it seems a promising approach to implement a more realistic framework in order to explore their social structures.…”
Section: Introductionmentioning
confidence: 99%